Effectiveness of Cognitive Ayurveda Therapy (CAT) against improving quality of life in patients with type 2 diabetes mellitus at RSU Royal Prima Medan - Ervin Rudianto Manao; Elia Br Sihombing; Firdayanti Gulo; Marina Stevi Tarihoran; Puspita Veronica Pardede (Institute of Computer Science (IOCS), 2023)
Maintaining normal blood sugar levels is not enough to treat diabetes mellitus. According to Yudianto, Hana, and Ida (2018), people with diabetes mellitus will carry the disease with them throughout their lives, affecting their health issues related to physical, mental, social, and environmental forms of quality of life. This research is compares persons including type 2 diabetes mellitus’ quality of life before and after CAT, in addition to calculate the effectiveness of cognitive Ayurvedic therapy in enhancing this quality of life. As reported by Lapau in Airlangga (2018), this research consists of a number of components that are combined to obtain information or facts to address research issues or questions. A significant diversity among the pre- and post-test values was found by the Paired Sample T-Test, with a significance level of p 0.000, 0.05 (2-tailed). There was a striking difference among the two tests, so the study’s null hypothesis (Ho) was denied and the alternative hypothesis (Ha) was acquired. Ayurveda therapy (CAT) has the highest level of effectiveness for improving respondents' quality of life, with very good results in health issues related to physical, mental, social, and environmental aspects. The Chi-Square pre- and post-test, with a p- value of 0.000, produced the following outcomes at RSU Royal Prima Medan, the persons including type 2 diabetes mellitus’ quality of life is significantly different previously and after treatments.